2019
DOI: 10.3389/fpsyg.2019.00873
|View full text |Cite
|
Sign up to set email alerts
|

No Job Demand Is an Island – Interaction Effects Between Emotional Demands and Other Types of Job Demands

Abstract: Emotional demands are an inevitable feature of human services, and suggested to be a defining antecedent for workers’ stress and ill health. However, previous research indicate that emotional demands can have a favorably association to certain facets of human service workers’ motivation and well-being. Furthermore, recent research report that the effect of emotional demands on workers’ health and well-being seem to be contingent on the parallel level of other job demands. Still, initial investigations of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 52 publications
1
22
1
Order By: Relevance
“…The nomological validity has been corroborated by operationalization of an extended JD-R model by the instrument with aspects of workability as outcome [11] as well as need for recovery [12] and also in relation to the newly introduced dimensions in the COPSOQ III of Work Engagement, Quality of Work [13] and Cyber Bullying [14]. Studies across different occupations have corroborated the internal consistency reliability and construct validity of the scales [11][12][13][15][16][17][18][19]. The ability to distinguish different groups (organizations with similar missions, work teams or occupational groups) has been demonstrated [20][21][22], as also the relevance of multilevel analyses and for intervention and organizational change studies [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 82%
“…The nomological validity has been corroborated by operationalization of an extended JD-R model by the instrument with aspects of workability as outcome [11] as well as need for recovery [12] and also in relation to the newly introduced dimensions in the COPSOQ III of Work Engagement, Quality of Work [13] and Cyber Bullying [14]. Studies across different occupations have corroborated the internal consistency reliability and construct validity of the scales [11][12][13][15][16][17][18][19]. The ability to distinguish different groups (organizations with similar missions, work teams or occupational groups) has been demonstrated [20][21][22], as also the relevance of multilevel analyses and for intervention and organizational change studies [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 82%
“…Future studies could also control for the potential effects of sociodemographic characteristics in the model, such as age. Previous studies have explored how emotional demands interact with other job demands (e.g., [ 52 ] and resources e.g., [ 29 ]) in predicting well-being and work engagement. This body of research suggests that when other types of demands are absent or low, or when appropriate resources are provided, emotional demands increase employees’ engagement with their role, or in other words, can be perceived as a positive “challenge”.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, given that emotional demands are closely tied to work tasks especially for service workers, these can be hard to avoid. Therefore, human resources practices that provide employees with working conditions that allow them to manage emotional demands, for example, by decreasing other types of job demands, e.g., [ 52 ], or by increasing job resources, e.g., [ 29 ], may promote engagement but not at the expense of their psychological well-being. Similarly, efforts to work on modifying PSC in organizations could increase employees’ resilience to the negative effects of emotional demands on psychological well-being, e.g., [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, emotional demands were found to contribute to higher levels of work engagement. This suggests that the emotional aspects of the work may be considered as challenges, contributing to the motivational process (e.g., Lepine et al, 2005;Bakker and Sanz-Vergel, 2013;Geisler et al, 2019a). In some contrast, the results showed that job demands were significantly related (negative direction) to job satisfaction.…”
Section: Discussionmentioning
confidence: 95%
“…Respondents who answer less than half of the questions were set as missing (cf. Berthelsen et al, 2017;Geisler et al, 2019a). Furthermore, the data collection included a scale for organizational resilience (Kantur and Iseri-Say, 2015), in order to assess employees' levels of credence in the organization's ability to respond to changes.…”
Section: Materials and Measuresmentioning
confidence: 99%